2022
DOI: 10.1016/j.jvacx.2021.100128
|View full text |Cite
|
Sign up to set email alerts
|

B cells do not play a role in vaccine-mediated immunity against Marek’s disease

Abstract: Background Marek’s disease virus (MDV), a highly oncogenic α-herpesvirus, is the etiological agent of Marek’s disease (MD) in chickens. The antiviral activity of vaccine-induced immunity against MD reduces the level of early cytolytic infection, production of cell-free virions in the feather follicle epithelial cells (FFE), and lymphoma formation. Despite the success of several vaccines that have greatly reduced the economic losses from MD, the mechanism of vaccine-induced immunity is poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…MD is associated with metabolic dysregulation ( 4 7 ), immunosuppression ( 8 14 ), neurological disorder ( 15 ), and CD4+ lymphoma formation in chickens ( 1 , 16 ). Because of MDV’s highly cell associated nature, it is believed that virus-specific T lymphocytes are critical in control of MD ( 17 , 18 ). Vaccination inhibits MD but fails to control MDV replication and shedding ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…MD is associated with metabolic dysregulation ( 4 7 ), immunosuppression ( 8 14 ), neurological disorder ( 15 ), and CD4+ lymphoma formation in chickens ( 1 , 16 ). Because of MDV’s highly cell associated nature, it is believed that virus-specific T lymphocytes are critical in control of MD ( 17 , 18 ). Vaccination inhibits MD but fails to control MDV replication and shedding ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has revealed that B cells do not play an essential role in vaccine-induced protection [ 47 ].The goal of the present study was to provide insight into the role of T cells in immunity mediated by vaccination. Using specific monoclonal antibodies, birds were depleted of CD4 + , CD8 + , or combined CD4 + /CD8 + T cells followed by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10 mg of spleen tissues were used for DNA isolation using Qiagen DNeasy Blood and Tissue Kit according to the manufacture’s recommendation. Skin DNA isolation was performed according to previously published protocol [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The respiratory route is one-way chickens are infected by MD as they inhale contaminated air [4]. The virus of Marek's disease is transported through the lungs to the lymphoid organs by attaching to macrophages and dendritic cells that have either been infected or have phagocytized the virus [9]. Following infection of the respiratory tract, pathogenesis occurs in several stages, including the initial cytolytic phase, latent phase, and late cytolytic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Despite low mortality, mild forms of Marek's disease can be immunosuppressive thus chickens are more susceptible to other diseases and potential sources of infection. Furthermore, [9] describe the clinical symptoms of MD for instance temporary paralysis, crippling, weight loss, blindness, depression, immunosuppression, and the formation of T cell lymphoma in visceral organs.…”
Section: Introductionmentioning
confidence: 99%